2020
DOI: 10.1002/nau.24588
|View full text |Cite
|
Sign up to set email alerts
|

OnabotulinumtoxinA for the treatment of neurogenic detrusor overactivity in children

Abstract: This study evaluated whether one (or more) of three doses of onabo-tulinumtoxinA were safe and effective to treat neurogenic detrusor overactivity (NDO) in children. Methods: This was a 48-week prospective, multicenter, randomized, doubleblind study in children (aged 5-17 years) with NDO and urinary incontinence (UI) receiving one onabotulinumtoxinA treatment (50, 100, or 200 U; not to exceed 6 U/kg). Primary endpoint: change from baseline in daytime UI episodes. Secondary endpoints: change from baseline in ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 25 publications
1
25
0
5
Order By: Relevance
“…Our finding of a significant improvement over the entire cohort regarding capacity and compliance is congruent with larger series which randomized children with neurogenic bladder to either 50, 100, or 200 U of Botox, and showed a dose‐dependent decrease in Pdetmax and bladder capacity 5 . In patients presenting with a high‐pressure bladder (Pdetmax > 20) with known risk of upper urinary tract deterioration, our data reveals this subgroup significantly improves their compliance and capacity.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our finding of a significant improvement over the entire cohort regarding capacity and compliance is congruent with larger series which randomized children with neurogenic bladder to either 50, 100, or 200 U of Botox, and showed a dose‐dependent decrease in Pdetmax and bladder capacity 5 . In patients presenting with a high‐pressure bladder (Pdetmax > 20) with known risk of upper urinary tract deterioration, our data reveals this subgroup significantly improves their compliance and capacity.…”
Section: Discussionsupporting
confidence: 88%
“…4 Botox, as a next-step therapeutic agent, helps improve these urodynamic parameters by improving capacity, compliance, end-fill maximum detrusor pressure (Pdetmax) and neurogenic detrusor overactivity (NDO). [5][6][7] While Botox may offset or delay the need for augmentation enterocystoplasty, 8 we must acknowledge that not all patients respond favorably to Botox injections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high rate of urinary continence can be achieved, with improvements in urodynamic parameters, including a reduction in detrusor pressure to <40 cmH 2 O and an increase in compliance to >20 mL/cmH 2 O, without major adverse events. In children with NDO, a dose of 200 U of Botox was well tolerated and showed greater efficacy in bladder pressure reduction and bladder capacity increase [ 94 ]. Children with a high detrusor pressure and low bladder compliance had a significantly greater improvement in compliance after detrusor Botox injections [ 95 ].…”
Section: Clinical Applications Of Botox On Pediatric Oab and Dv: Effi...mentioning
confidence: 99%
“…Onabotulinum toxin A showed positive efficacy and safety in children at doses up to 360 U. It was shown that 32%–100% of children achieved continence, detrusor pressure was reduced by 32% to 54%, and the maximum pressure was below the 40 cm H 2 O threshold[ 46 ].…”
Section: Management Of Nbd In Childrenmentioning
confidence: 99%